Working of Urban Co-Operative Banks in the Coastal Andhra Region of Andhra Pradesh - Sudhakara Rao, K. (Indian Journal of Finance, 2015)
The urban co-operative movement was active in the Coastal Andhra region of Andhra Pradesh when it was a part of the Madras State. Though all the districts in the region are geographically identical, other variables like demographic characteristics, number of towns, and industrial progress vary from district to district. They have had a significant effect on the setting-up and distribution of Urban Co-operative Banks among different districts of the region.Working capital may be regarded as the life blood of a business. The extent of business operations of Urban Co-operative Banks depend on the volume of working capital and net profit. The greater the working capital, the greater is the efficiency of the bank ; thus, the working capital is an important factor in the functioning of urban co-operative banks. The present study was a fact finding and comparative study aimed at analyzing the working of selected (8) Urban Co-operative Banks in the Coastal Andhra region of Andhra Pradesh over a period of 10 years (i.e. from 2003-04 to 2012-13) with the help of select indicators like share capital, reserves, deposits, owned funds, working capital, loans and advances, and net profit of the sample banks.